(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Motor fitness is a present aptitude for physical skills, includes strength and co-ordination enriches today’s Manpower in players performance. The study focuses on selected motor fitnesscomponents to ensure the playing ability among low and high performers of Statelevel Football players. To achieve this study, One hundred and fifty men Football players were randomly selectedas subjects from Haryana State level men Football Tournament held at Karnal in2008-09. Their age ranged from20 to 25 years. Selected subjects were classifiedinto three equal groups of each fifty members. Group 1 served as -Karnal Team,Group-II as Gurgaon and Chandigarh Team and Group III Kaithal and Meerut Team.All the subjects were oriented the purpose of the test and procedure ofconducting this test. Regular activities and training were given that aplombthe player’s ability to perform the game.Questionnaire preparation was also done by our Research Scholar with the reference to the review of the literature. The investigator hasprovided onto the following selected motor fitness variables such as Cardio-vascularEndurance, Speed, Agility and Explosive Power. The data is collected with thehelp of five PhD Scholars, Department of Physical Education who were wellversed with the conduct of test and collections under the direct supervision of ourResearch Scholar. Resulting data will be collected before and after the competition and statistically analyzed using ANOVA andDMRT. Hence the study concluded thatplaying ability solely depends on the physical fitness, stress free mind morethan that it relates the socio-economic status to perform the better strategyof playing games.